1991
DOI: 10.1111/j.1432-1033.1991.tb15816.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a negatively charged amino acid in thioredoxin modifies its reactivity with chloroplastic enzymes

Abstract: A new over-expression system has been set up for Escherichiu coli thioredoxin, yielding 55 mg purified protein/ 10 g fresh cells. This system has been used to produce thioredoxin modified by site-directed mutagenesis. Taking advantage of the structural and enzymatic similarity between E. coli and spinach m-type thioredoxin, Asp61 of E. coli thioredoxin has been changed into Asn in order to investigate the impact of the suppression of a charged residue on the interaction of thioredoxin with target enzymes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…Some reports show the essential role of available positively charged groups flanking the Trx active center in some Trxdependent processes (Eklund et al, 1991;Brandes et al, 1993). Moreover, site-directed mutagenesis has demonstrated the harmful effect of Trx negatively charged amino acids in the enzyme activation (Lamotte-Guery et al, 1991).…”
Section: Results and Dlscusslonmentioning
confidence: 99%
“…Some reports show the essential role of available positively charged groups flanking the Trx active center in some Trxdependent processes (Eklund et al, 1991;Brandes et al, 1993). Moreover, site-directed mutagenesis has demonstrated the harmful effect of Trx negatively charged amino acids in the enzyme activation (Lamotte-Guery et al, 1991).…”
Section: Results and Dlscusslonmentioning
confidence: 99%
“…Thus, alterations of nonfunctional thioredoxins and target enzymes should ensue variations of the final catalytic activity. Accordingly, LamotteGuery et al found that the mutant D61N trx was more efficient than trx in the stimulation of chloroplast fructose-l,6-bisphosphatase but it did not match trx-f [5]. Conversely, the contribution of the enzyme to the activation process has not been explored in previous studies.…”
Section: Introductionmentioning
confidence: 97%
“…Recombinant E. coli thioredoxin was purified as in Ref. 15. NADP-MDH activity was measured on aliquots, at 30°C, by following the decrease in absorbance at 340 nm, in a standard assay mixture (1 ml) containing 100 mM TrisHCl, pH 7.9, 780 M oxaloacetate, and 140 M NADPH.…”
Section: Methodsmentioning
confidence: 99%